Medical Anthropology’s ‘ownership of the body’ and the medicalisation of Social Anthropology - Bernhard Hadolt (AM. Rivista della Società Italiana di Antropologia Medica, 2001)
Medical Anthropology’s ‘ownership of the body’ and the medicalisation of Social Anthropology